2021
DOI: 10.7554/elife.69832
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, cellular, and structural characterization of the membrane potential-dependent cell-penetrating peptide translocation pore

Abstract: Cell-penetrating peptides (CPPs) allow intracellular delivery of bioactive cargo molecules. The mechanisms allowing CPPs to enter cells are ill-defined. Using a CRISPR/Cas9-based screening, we discovered that KCNQ5, KCNN4, and KCNK5 potassium channels positively modulate cationic CPP direct translocation into cells by decreasing the transmembrane potential (Vm). These findings provide the first unbiased genetic validation of the role of Vm in CPP translocation in cells. In silico modeling and live cell experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 154 publications
(236 reference statements)
0
25
0
Order By: Relevance
“…Still, the membrane potential seems to play a role in cells, as demonstrated by a recent experimental study highlighting the role of ion channels in generating permeable pores. 22 Moreover, very recent experiments with giant unilamellar vesicles (GUVs) composed of neutral PC lipids at very low ARCPP concentrations have actually shown pore-free translocation of ARCPPs, 35 , 36 in contrast to previous literature.…”
Section: Introductionmentioning
confidence: 97%
“…Still, the membrane potential seems to play a role in cells, as demonstrated by a recent experimental study highlighting the role of ion channels in generating permeable pores. 22 Moreover, very recent experiments with giant unilamellar vesicles (GUVs) composed of neutral PC lipids at very low ARCPP concentrations have actually shown pore-free translocation of ARCPPs, 35 , 36 in contrast to previous literature.…”
Section: Introductionmentioning
confidence: 97%
“…This result suggests that Tat- t MeCP2 gains entry into cells, albeit less efficiently ( Extended Data Fig. 6b ), via a different subpopulation of endosomes 48 or one or more non-endosomal pathways 49 .…”
Section: Resultsmentioning
confidence: 98%
“…This result suggests that Tat-tMeCP2 gains entry into cells, albeit less efficiently (Extended Data Fig. 6b), via a different subpopulation of endosomes 48 or one or more non-endosomal pathways 49 . Delivered ZF-tMeCP2 interacts with partner proteins in the NCoR/SMRT complex Next we explored the function of tMeCP2 proteins delivered to the nucleus of CHO-K1 cells, which express low levels of endogenous MeCP2 (Extended Data Fig.…”
Section: Zf-tmecp2 Accesses a Hops-dependent Portal For Endosomal Rel...mentioning
confidence: 98%
“…It has been shown that ZFP penetrates cells through macropinocytosis and, to a lesser extent, caveolindependent endocytosis (Gaj et al, 2014). In addition, TAT or other CPPs may penetrate cells through water pore-mediated direct translocation (Trofimenko et al, 2021). Therefore, one may envision that fusion of CPPs can compromise the cell-targeting specificity of BoNTA proteins.…”
Section: Discussionmentioning
confidence: 99%